2020
DOI: 10.3390/nano10030415
|View full text |Cite
|
Sign up to set email alerts
|

Commitment of Autologous Human Multipotent Stem Cells on Biomimetic Poly-L-Lactic Acid-Based Scaffolds Is Strongly Influenced by Structure and Concentration of Carbon Nanomaterial

Abstract: Nanocomposite scaffolds combining carbon nanomaterials (CNMs) with a biocompatible matrix are able to favor the neuronal differentiation and growth of a number of cell types, because they mimic neural-tissue nanotopography and/or conductivity. We performed comparative analysis of biomimetic scaffolds with poly-L-lactic acid (PLLA) matrix and three different p-methoxyphenyl functionalized carbon nanofillers, namely, carbon nanotubes (CNTs), carbon nanohorns (CNHs), and reduced graphene oxide (RGO), dispersed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 57 publications
(78 reference statements)
0
21
0
Order By: Relevance
“…Its presence in a poly(lactic-co-glycolic acid (PLGA) film increased its hydrophilicity and enhanced neuronal differentiation of neuronal stem cells (NSCs) [58]. In our lab we [47,59] designed composite poly-L-lactic acid (PLLA) scaffolds with different carbon Figure 3. Assembly of RGO-cellulose hybrid paper through deposition of GO followed by in situ reduction [55].…”
Section: Two-dimensional Scaffoldsmentioning
confidence: 99%
See 3 more Smart Citations
“…Its presence in a poly(lactic-co-glycolic acid (PLGA) film increased its hydrophilicity and enhanced neuronal differentiation of neuronal stem cells (NSCs) [58]. In our lab we [47,59] designed composite poly-L-lactic acid (PLLA) scaffolds with different carbon Figure 3. Assembly of RGO-cellulose hybrid paper through deposition of GO followed by in situ reduction [55].…”
Section: Two-dimensional Scaffoldsmentioning
confidence: 99%
“…Its presence in a poly(lactic-co-glycolic acid (PLGA) film increased its hydrophilicity and enhanced neuronal differentiation of neuronal stem cells (NSCs) [ 58 ]. In our lab we [ 47 , 59 ] designed composite poly-L-lactic acid (PLLA) scaffolds with different carbon nanostructures (CNS) as filler—namely RGO, carbon nanohorns (CNH) and CNT—covalently functionalized with p-methoxyphenyl (PhOMe) groups in order to improve biocompatibility, and the electrical and mechanical properties of materials. RGO- and CNH-based scaffolds (RGO-PhOMe and CNH-PhOMe respectively) showed promising activity in enhancing the expression of myogenic markers during human circulating multipotent stem cell (hCMCs) differentiation.…”
Section: Graphene-based Scaffoldsmentioning
confidence: 99%
See 2 more Smart Citations
“… 111 Graphene could act as a biocompatible and conductive substrate for human induced pluripotent stem cells (hiPSCs) and mimic the biomimetic conductive cardiogenic niche to promote the self-renewal and cardiac differentiation of hiPSCs. 112 , 113 It is reported that highly conductive GBNs, such as the carbon nanotubes, could enhance the neuronal differentiation of multipotent autologous cells in most cases. On the contrary, several GBNs-conjugated composite scaffolds which are less conductive appeared to boost the expression of myogenic-lineage marker genes.…”
Section: Graphene and Graphene-based Nanomaterialsmentioning
confidence: 99%